2015
DOI: 10.1007/s13205-015-0318-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and antagonistic potential of marine microbes collected from south-west coast of India

Abstract: The diversity of some of the culturable microorganisms associated with marine flora and fauna collected off Vizhinjam and Mulloor coast of South India was evaluated and their bioactive production potential determined. From a total of 24 bacteria, 4 actinomycetes and 8 fungi isolated from diverse marine sources, five bacterial species-BLM3, BSP2, BCS1, BCS4 and BMA6 showed inhibitory activity against at least one of the tested pathogens viz., Klebsiella pneumonia KU1, Pseudomonas aeruginosa VL3, Salmonella ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…In previous studies, the best preparation of flavonoids from Malus domestica , Launaea procumbens , kumquat , and Spanish olive cultivars was obtained with the use of ethyl acetate [ 8 , 30 , 35 , 36 ]. It has been reported that ethyl acetate is the optimal reagent for isolation of active substances from plant materials [ 37 , 38 ]. In present study, it was confirmed that among all the employed organic solvent mixtures, ethyl acetate was the most effective solvent for the preparation of flavonoid-rich extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, the best preparation of flavonoids from Malus domestica , Launaea procumbens , kumquat , and Spanish olive cultivars was obtained with the use of ethyl acetate [ 8 , 30 , 35 , 36 ]. It has been reported that ethyl acetate is the optimal reagent for isolation of active substances from plant materials [ 37 , 38 ]. In present study, it was confirmed that among all the employed organic solvent mixtures, ethyl acetate was the most effective solvent for the preparation of flavonoid-rich extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Antagonists have also been isolated from fruit, and these have shown potential for exploitation as BCA of postharvest diseases [14]. The marine environment is also a deposit of new bioactive compounds; thousands of unique compounds have been isolated from this environment [102,103]. In recent years, any bioactive compound and different samples from marine environments have been searched for.…”
Section: Search For New Antagonistsmentioning
confidence: 99%
“…Species of Bacillus are easy to culture and can survive under harsh conditions. Bioactive metabolite and enzyme production is common feature of Bacillus species (Mondol et al 2013;Sinimol et al 2016). In addition to Bacillus, Staphylococcus is another representative of Firmicutes in this study, and is already known to produce antimicrobial metabolites (Barbieri et al 2005;Mani et al 2016).…”
Section: Discussionmentioning
confidence: 93%